2021
DOI: 10.3390/nano11123164
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Water-Processable Polyimide Binders with High Adhesion to Silicon Anodes for Lithium-Ion Batteries

Abstract: Silicon is an attractive anode material for lithium-ion batteries (LIBs) because of its natural abundance and excellent theoretical energy density. However, Si-based electrodes are difficult to commercialize because of their significant volume changes during lithiation that can result in mechanical damage. To overcome this limitation, we synthesized an eco-friendly water-soluble polyimide (W-PI) precursor, poly(amic acid) salt (W-PAmAS), as a binder for Si anodes via a simple one-step process using water as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In this study, to confirm the compatibility of MPS with a highly negative ζ potential of more than −20 mV in the PAA matrix, water-soluble BPDA- p PDA-based PAAs having positive or negative charges at the end groups were prepared. As shown in the molecular structure of Figure S6a, PAA-A and PAA-C were eco-friendly polymerization in water as a solvent as following our previous studies. , When PAA-A and PAA-C are solubilized in water, the −NH 2 group has a positive charge in the −NH 3 + state, and the −COOH group has a negative charge in the −COO – state. Since the characteristic −COOH group of PAA in the main chain forms ammonium salt foam with DMIZ, the state of charge in each PAA is determined by the type of end-terminated group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to confirm the compatibility of MPS with a highly negative ζ potential of more than −20 mV in the PAA matrix, water-soluble BPDA- p PDA-based PAAs having positive or negative charges at the end groups were prepared. As shown in the molecular structure of Figure S6a, PAA-A and PAA-C were eco-friendly polymerization in water as a solvent as following our previous studies. , When PAA-A and PAA-C are solubilized in water, the −NH 2 group has a positive charge in the −NH 3 + state, and the −COOH group has a negative charge in the −COO – state. Since the characteristic −COOH group of PAA in the main chain forms ammonium salt foam with DMIZ, the state of charge in each PAA is determined by the type of end-terminated group.…”
Section: Resultsmentioning
confidence: 99%
“…Following our previous studies, the BPDA/PDA-based PAA-A or PAA-C were prepared using a one-step polymerization process in an aqueous solution with 1,2-dimethylimidazole (DMIZ), which enables the formation of an ammonium salt with the carboxylate group of PAA. , It was synthesized in a three-neck flask equipped with a mechanical stirrer under a nitrogen atmosphere. By a 0.01 molar ratio over the equimolar condition, dianhydride (BPDA) and diamine (PDA) monomers were used in a slightly excess amount to terminate the end group with the desired charge.…”
Section: Methodsmentioning
confidence: 99%
“…Water-borne poly(amic acid) salts (W-PAASs) have been proposed for the preparation of polymeric precursors for PI via an eco-friendly process because of the use of water as a synthetic medium. 6,[29][30][31][32][33][34] This facile strategy provides a one-pot procedure for polymerizing dianhydride and diamine monomers in aqueous media with organic bases. The single-step reaction and use of water as a polymerizing medium provide economic and ecological efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…33 Our group has also contributed to providing a synthetic route for W-PAAS varnishing by monomers in the presence of 1,2-dimethylimdazole as the organic base. 7,31,32 We proposed the fabrication of an organic thin-film transistor (OTFT) with a pinhole-free polyimide dielectric layer by casting an aqueous solution using simple spin-casting. 7 Nevertheless, few combinations of chemical ingredients have been suggested, limiting the potential of W-PAAS as a polymeric platform with diverse functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been further demonstrated that Si anodes prepared with polymeric binders containing polar moieties (e.g., hydroxyl or carboxyl groups), such as poly­(acrylic acid) (PAA) or sodium alginate (Na-alginate), exhibit far superior electrochemical performance than Si electrodes prepared from non-polar PVdF. Contrary to non-polar binders, those having functional groups possess enhanced adhesion due to their ability to form hydrogen bonds between polar groups and the partially hydrolyzed SiO 2 surface layer on the Si particles. Nonetheless, non-cross-linked binders are not capable of fully compensating the volume expansions as the Si particles tend to slip between the polymer chains. Consequently, Si particles embedded in the polymer matrix cannot recover their pristine state after continuous expansion/shrinkage, which results in a loss of structural integrity and capacity fading. , To address this issue, cross-linked binders, which form a 3D network structure around the Si particles, have been introduced.…”
Section: Introductionmentioning
confidence: 99%